Laterality of radiographic osteoarthritis of the knee. Issue 3 (4th May 2017) - Komatsu, Daigo; Ikeuchi, Kazuma; Kojima, Toshihisa; Takegami, Yasuhiko; Amano, Takafumi; Tsuboi, Masaki; Ishiguro, Naoki; Hasegawa, Yukiharu
ABSTRACT: There are few reports of the laterality in radiological knee osteoarthritis (ROA). This study aimed to evaluate laterality in terms of the minimum joint space width (mJSW) and osteophyte areas (OFs) in a cross-sectorial general population screen and elucidate the association between laterality and risk of osteoarthritis. We enrolled 330 participants (mean age 64.6 years) and examined the presence of ROA (Kellgren–Lawrence grade ≧ 2) laterality in terms of the mJSW and OF on the medial tibia using auto-measuring software. Moreover, we examined the association between laterality and leg dominance. The right and left medial mJSWs were 4.02 ± 0.98 mm and 4.05 ± 1.01 mm, respectively, showing no laterality; the laterals were also similar. The participants who had osteophytes ≥1 mm 2 in the right, left, and bilateral knees were 15, 37, and 57 respectively, with osteophytes being significantly more common in the left knee. The OF was significantly larger in the left knee. Conversely, the medial and lateral mJSWs and OF did not differ according to leg dominance. The prevalence of ROA was higher and the OF was more pronounced in the left knee. However, the mJSW showed no laterality. Additionally, the mJSW and OF showed no differences according to leg dominance.